THE IMPACT OF SOCIAL MEDIA MARKETING (SMM) ON CONSUMER EXPERIENCE AND CONSUMER BRAND ENGAGEMENT - Ranti, Tiara Mega (Jurnal Manajemen dan Profesional, 2025)
This study investigates the impact of Social Media Marketing (SMM) on consumer experience and consumer brand engagement using Fore Coffee as a case study. Social media, especially Instagram, plays a vital role in modern business strategies to foster interaction with consumers. This research explores the influence of five key elements of SMM: entertainment, interaction, trendiness, customization, and electronic word-of-mouth (EWOM), on consumer experience and their subsequent engagement with brands. The findings indicate that all five factors positively affect consumer experience, which in turn enhances consumer brand engagement. Data was collected through a survey of 275 Fore Coffee customers, analyzed using Structural Equation Modeling (SEM). Results show that EWOM has the strongest impact on consumer experience, leading to significant consumer brand engagement.